Renal sarcoidosis: renal pathology guides diagnosis and prognosis - Aichun Liu; Yina Wang; Yu Yan; Bao Dong; Meishun Cai; Li Zuo (Diagnostic Pathology)
Abstract Background While many studies have reported renal involvement in sarcoidosis, there is limited description of the pathological manifestations of renal sarcoidosis (RS). This study aimed to explore the standardized pathological diagnosis of RS while evaluating the relationship among pathology, clinical manifestations, and prognosis. Methods We conducted a retrospective, single-center study of RS in renal biopsy cases treated in our department between January 2019 and December 2023. Results We identified 5 patients (4 men, 1 woman; median age 52 years, IQR 36–61 years). Two patients were diagnosed with non-caseating granulomatous interstitial nephritis (GTN), while two patients were diagnosed with tubulointerstitial nephritis without granulomas (TIN), and one patient was diagnosed with acute tubular necrosis (ATN). The grading of tubulointerstitial acute inflammation revealed 2 cases (case 4 and case 5) graded as (+++), with serum creatinine levels greater than 900 µmol/L at onset. Additionally, there were 2 cases (case 2 and case 3) gradedas (+), and 1 case (case 1)graded as (-), with serum creatinine levels approximately 400 µmol/L at onset. All 5 cases exhibited an interstitial fibrosis grade of (-). However, in the second renal biopsy following recurrence in case 4, the interstitial fibrosis grade increased to (++). In two patients with GTN, immunohistochemical staining revealed that the infiltrating lymphocytes were predominantly CD4 + T cells, which formed nodular granulomas and were surrounded by CD8 + T cells. A favorable response to steroid therapy was noted in all cases, especially in case 1, 2, and 3. Conclusions The pathological manifestations of RS primarily consist of acute TIN with or without granuloma formation. Quantifying the pathological grade may assist in guiding treatment decisions and predicting prognosis.